Kunsthaus Zürich : In den Alpen. - Becker, Christoph; Bezzola, Tobia; Hug, Catherine; Exhibition. In den Alpen. Kunsthaus Zürich. 2006-10-06. 2007-01-02 (Zürich : Kunsthaus Zürich, 2006)
Bachmann, Carolyn ; Banz, Stefan ; Baselgia, Guido ; Baud-Bovy, Auguste ; Baudevin, Francis ; Bauknecht, Philipp ; van den Berg, Christoph ; Bernhardsgrütter, Anton ; Bertier, Charles ; Birmann, Samuel ; Bleiker, Heinrich ; Bleiker, Ulrich ; Böcklin, Arnold ; Bonvicini, Monica ; Braas, Sonja ; Braun, Adolphe ; Brunner, Emil ; Büchel, Christoph ; Burkhard, Balthasar ; Calamé, Alexandre ; Carron, Valentin ; Disteli, Martin ; Doig, Peter ; Doré, Gustave ; Exchaquet, Charles-François ; Fabrizio, Leo ; Faure, Nicolas ; Flechtner, Thomas ; Füssli, Johann Melchior ; Giacometti, Alberto ; Giacometti, Giovanni ; Giovanoli, Samuele ; Godard, Jean-Luc ; Guétal, Laurent ; Guigon, Charles-Louis ; Hechenblaikner, Lois ; Hefti, Raphaël ; Hodler, Ferdinand ; Imhof, Eduard ; Iselin, Roland ; Kles, Henning ; Klinger, Max ; Koch, Joseph Anton ; Koller, Rudolf ; Lartigue, Jacques-Henri ; Linke, Armin ; Madörin, Tobias ; Main, Elizabeth ; Martin, John ; Masuyama, Hiroyuki ; Matter, Herbert ; Müller, Albert ; Müller, Josef Felix ; Parr, Martin ; Rainer, Arnulf ; Ralske, Jan ; Regli, Peter ; Richter, Gerhard ; Rinaldi, Renato ; Ruskin, John ; Schibli, Daniel ; Schürmann, Filib ; Schütte, Thomas ; Segantini, Giovanni ; Senn, Sandra ; Speiser, Gottlieb ; Spinatsch, Jules ; Stallaerts, Helmut ; Strba, Annelies ; Studer, Monica ; Taut, Bruno ; Tettamanti, Joël ; Su-Mei Tse ; Wenk, Niklaus ; Wurm, Erwin ; Zanini, Piero ; Zaugg, Rémy
Duits
boek
Keywords: Alpen